Light Symbolism in Gentile da Fabriano’s Vatican Annunciation - Hodne, Lasse (Eikón / Imago, 2014)
Gentile da Fabriano’s Annunciation in the Vatican Pinacoteca is one of the clearest and most interesting visualizations of a famous metaphor from Medieval hymn literature that compares Mary’s hymen to the glass of a window. The painting uniquely combines three elements: rays of light, a Gothic tracery window, and the shape of the window impressed on the Virgin’s body. Gentile’s painting is the culmination of a development in Tuscan art that can be traced back at least until about 1370. This makes it part of an Italian tradition of visualizing the so-called ut vitrum metaphor that must antedate analogous examples from Flemish art.